#TITLE_ALTERNATIVE# - HILMAN (NIM : 12308037), ROSTANDAR
Gravity method is one of geophysical exploration method which measure gravitational field variation that is caused by earth’s rock density differences. Variation of density can be derivates using this method, in order to interpret either the form or the geometry of the anomaly source. The determination of basin’s configuration based on gravitational data is highly required in order to do preliminary exploration in area with hydrocarbon prospect. Residual anomaly can be modeled for producing the depth of basement layer to determine the basin’s configuration. Calculation of gravitational responses from the initial model (forward modeling) is executed with 3-dimensional calculation, assuming every grid as a vertical rectangular prism with constant value of density. Thickness correction or maximum depth each the grid is based on the difference between calculation data and observation data (misfit). Using guided random search algorithm, 3D inverse modeling of gravity data is executed utilizing the technical computing program in MATLAB. Model solution is determined iteratively in order to obtain the optimum solution which is associated with minimum global of the high-dimensional space model. Result of this 3D inverse modeling can be interpreted to estimate the depth of basement’s top layer and the basin’s configuration in the research area.